2007
DOI: 10.1016/j.febslet.2007.07.052
|View full text |Cite
|
Sign up to set email alerts
|

3H‐serotonin as a marker of oscillatory insulin secretion in clonal β‐cells (INS‐1)

Abstract: Serotonin release from preloaded pancreatic b-cells has been used as a marker for insulin release in studying exocytosis from single cells using the amperometric technique. We found that single pancreatic b-cells exhibited oscillations in exocytosis with a period of 1-1.5 min as measured amperometrically by serotonin release. We also show that 3 H-serotonin can be used to monitor exocytosis from intact and streptolysin-O permeabilized clonal insulin-secreting cells preloaded with labeled serotonin and that ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Briefly, cells co-cultured for 24 h were washed with KRB buffer containing 2.75 mM glucose, equilibrated in this solution for 45 min, and then permeabilized using 3.2 units/ml streptolysin-O (Sigma) for 30 min on ice as described previously (24,26). Cells were then washed and equilibrated with an EGTA-buffered 0.1 M free Ca 2ϩ , 140 mM K ϩ -glutamate solution for 10 min at 37°C and next incubated with the same EGTA-buffered solution with either 0.1 M or 10 M free Ca 2ϩ for 15 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, cells co-cultured for 24 h were washed with KRB buffer containing 2.75 mM glucose, equilibrated in this solution for 45 min, and then permeabilized using 3.2 units/ml streptolysin-O (Sigma) for 30 min on ice as described previously (24,26). Cells were then washed and equilibrated with an EGTA-buffered 0.1 M free Ca 2ϩ , 140 mM K ϩ -glutamate solution for 10 min at 37°C and next incubated with the same EGTA-buffered solution with either 0.1 M or 10 M free Ca 2ϩ for 15 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Findings showed that serotonin loaded into the beta cells localizes to the insulin secretory granules and is additionally co-released with it [26,27]. These authors demonstrated that there is little exocytotic activity of insulin + 5-HT at the basal glucose level, but increasing the sugar concentration results in increased insulin release from perfused beta cells.…”
Section: Peripheral Mechanismsmentioning
confidence: 76%
“…It is incorporated into the insulin granules of the former [22,23], at which level exerts a modulatory effect [24][25][26][27]. Conversely, 5-HT facilitates the secretion of glucagon from the alpha cells into the blood stream [21,[28][29][30].…”
Section: Peripheral Mechanismsmentioning
confidence: 99%
“…5-HT, a marker of oscillatory insulin secretion [29] , is synthesized within β-cells and stored together with insulin in the secretory β-granules. Intracellular 5-HT regulates insulin secretion via serotonylating GTPases including Rab3a and Rab27a, which induces co-release of 5-HT and insulin [37] .…”
Section: Discussionmentioning
confidence: 99%
“…When the cells grew to 70% confluence, the cells were incu- [29,30] . The cells were collected for assaying intracellular insulin and 5-HT levels.…”
Section: Pharmacokinetics Of Pravastatin and Paroxetine In Diabetic Ratsmentioning
confidence: 99%